Kincir Angin Tipe Vertikal Dengan Menggunakan Natural Convection Ruang Pengering Sebagai Penggerak - Titania Hindra, Gabrielle; Wijaya Kusuma, I. G. B.; ., Suarnadwipa (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Kata kunci: : Konveksi alami, CFD, aerofoil, airfoil Abstract Indonesia is located on the equator, so Indonesia has an abundant source of solar energy. To take advantage of solar energy, we can use various ways, one of which is by using natural convection. Natural convection (natural convection) or free convection (free convection), occurs because fluids that experience a temperature difference flow naturally without any influence or assistance from the surroundings. This research was carried out in a simulation using the Autodesk CFD application which will vary 3 conditions, namely hot weather which has a temperature of 40 ° C, sun intensity 987.64 watt /m2, then cloudy weather which has a temperature of 36 ° C solar intensity 756.50 watt/m2. and rainy weather which has a temperature of 26 ° C, sun intensity 390.90 watt/m2. Also conducted testing of 3 types of airfoils, namely NACA 0012, 0018 and 4418 using the AeroFoil 3.2 application, the input in these applications is a wind speed of 1.1 m / s2 and a chord length of 0.2 m. The results of this research show that natural heat transfer can produce fluid velocity flow. The highest velocity of fluid flow produced is found in hot weather, namely 2.49 m/s2, then the lowest is produced by rainy weather at 1.13 m/s2 and theoretically at 1,22 m/s2 then the best NACA type to be used as an airfoil in vertikal type windmills is NACA 4418 which has the highest drag and lift coefficient then produces a drag force of 0.027509214 N, a lift force of 0.012210356 N, and has a thrust force of 0.3 N at a cross-sectional area of 151.51 m2. . Keywords: Natural convection, CFD, aerofoil, airfoil